Pengaruh Kepribadian dan Komitmen Organisasi terhadap Organizational Citizenship Behavior - Purba, Debora Eflina; Seniati, Ali Nina Liche (UI Scholars Hub, 2004)
The Influence of Trait Personality and Organizational Commitment on Organizational Citizenship Behavior. Team effectivity is determined by it’s members ability to communicate, collaborate, share information, and tolerate differences among them. All the abilities are examples of organizational citizenship behavior (OCB). The purpose of this research is to investigate antecedents of OCB on employees in a process industry in Indonesia. The result showed the significant effects of trait personality and organizational commitment on OCB in Indonesia.